Pengembangan LKS Berorientasi High Order Thinking Skills pada Materi Larutan Elektrolit dan Non Elektrolit - Jehan Sari Dewi; Marina Setyarini; Tasviri Efkar (Universitas Lampung, 2018)
The purpose of this research is to 1) describe characteristics of student worksheets oriented on High Order Thinking Skills (HOTS) that developed, 2) describe teacher’s response to student worksheets that developed and 3) describe students’ response to student worksheets that developed. The research method was Research and Development (RD). The validation result was obtained average percentage on aspects in suitability of content, construction, and readability were 84.30% , 84,00% and 81,50% respectively. The result of teacher’s response was obtained average percentage on aspects in suitability of content, construction, and readability were 88,30%, 93,00% and 92,50% respectively. The result of students’ responsewas obtained average percentage on aspects inreadability and attractiveness were 84,36% and 81,50% respectively. Based on validation result, teacher’s response and students’ response on aspects in suitability of content, construction, readability and attractiveness, student worksheets that developed categorized in very high and showed that the student’ worksheets was proper to be used on learning.Tujuan penelitian pengembangan ini untuk 1) mendeskripsikan karakteristik LKS berorientasi HOTS yang dikembangkan, 2) mendeskripsikan tanggapan guru mengenai LKS yang dikembangkan dan 3) mendeskripsikan tanggapan siswa mengenai LKS yang dikembangkan. Metode penelitian yang digunakan adalah metode penelitian Research and Development (RD) dari Sukmadinata (2011). Hasil validasi ahli pada aspek kesesuaian isi, konstruksi, dan keterbacaan LKS diperoleh rata-rata persentase sebesar 84.30% , 84,00% dan 81,50%. Hasil tanggapan guru terhadap aspek kesesuaian isi, konstruksi, dan keterbacaan diperoleh rata-rata persentase sebesar 88,30%, 93,00% dan 92,50%. Hasil tanggapan siswa terhadap aspek keterbacaan dan kemenarikan diperoleh rata-rata persentase sebesar 84,36% dan 81,50%. Berdasarkan hasil validasi ahli, tanggapan oleh guru dan siswa terhadap aspek kesesuaian isi, konstruksi, keterbacaandan kemenarikan, LKS yang dikembangkan dikategorikan sangat tinggi sehingga LKS layak untuk digunakan dalam pembelajaran. Kata kunci: keterampilan berpikir tingkat tinggi, LKS, larutan elektrolit dan non elektrolit